2017
DOI: 10.1111/are.13484
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mapping and socio-economic status of cage culture: Towards balancing lake-use and culture fisheries in Lake Victoria, Kenya

Abstract: Mapping of lacustrine aquaculture and socio-economic assessment of cage farmers operations can be employed as decision support tools in an integrated fashion for fisheries management. We simultaneously mapped and reported the location of cages and characterized socio-economic and indicators of cage farming in Lake Victoria, Kenya. Structured questionnaires and interviews from cage farmers generated socio-economic data and management information. Vital water quality parameters were analyzed in selected sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 23 publications
2
81
0
Order By: Relevance
“…So, cage farming could provide an excellent opportunity for riparian communities that presentlyrely upon over-harvested commercial fisheries to engage in gainful livelihoods. However, cage culture remains a male-dominated activity, with the majority of owners being aged between 36 and 45 years (Aura et al, 2017). As a result, this middle-level age group is the major beneficiary of cage culture in Lake Victoria.…”
Section: G Rowing the B Lue Economymentioning
confidence: 99%
See 2 more Smart Citations
“…So, cage farming could provide an excellent opportunity for riparian communities that presentlyrely upon over-harvested commercial fisheries to engage in gainful livelihoods. However, cage culture remains a male-dominated activity, with the majority of owners being aged between 36 and 45 years (Aura et al, 2017). As a result, this middle-level age group is the major beneficiary of cage culture in Lake Victoria.…”
Section: G Rowing the B Lue Economymentioning
confidence: 99%
“…This is mainly because most farmers prefer such zones because they provide ease of access opportunities for close supervision, and because they are sheltered from potentially damaging winds and currents. However, it has been shown that the location of these cages in the water body may interfere with water circulation (Aura et al, 2017 . For example, the development of pen farming of milkfish in Laguna De Bay, Philippines, reduced fishers' access to traditional fishing grounds thereby leading to conflicts (Marte, Cruz & Flores, 2000).…”
Section: Ag E Culture S Itingmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to regulate aquaculture growth is a major challenge facing development of the sector in the AGLs (Njiru et al, ). There is a need for proper planning procedures to be formulated and implemented both locally and basin‐wide and linked to best practice guidelines (Aura et al, ). These guidelines should provide optimal production practices and link to environmental monitoring and compliance procedures.…”
Section: Sustainable Fisheries and Aquaculturementioning
confidence: 99%
“…Enhancing nutrient status as illustrated by the eutrophication problems in L. Victoria can lead to a number of undesirable effects (Hecky, Mugidde, Ramlal, Talbot & Kling, 2010). Current development of in situ fish cage aquaculture requires further monitoring and environmental risk assessment (Aura et al, 2018;Kashindye et al, 2015).…”
Section: The Way Forward and Prognosis For Sustainabilitymentioning
confidence: 99%